2003
DOI: 10.1121/1.1635407
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties associated with parameter estimation in atmospheric infrasound arrays

Abstract: This study describes a method for determining the statistical confidence in estimates of direction-of-arrival and trace velocity stemming from signals present in atmospheric infrasound data. It is assumed that the signal source is far enough removed from the infrasound sensor array that a plane-wave approximation holds, and that multipath and multiple source effects are not present. Propagation path and medium inhomogeneities are assumed not to be known at the time of signal detection, but the ensemble of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 10 publications
0
71
0
Order By: Relevance
“…While a general agreement between the observed and predicted microbarom azimuths is found, similar to earlier studies by Walker [2012] and Assink et al [2014b], differences up to~20°are often observed. These differences could be associated with approximations in long-range propagation modeling (azimuth uncorrected for transversal wind effects and range-independent atmospheric profiles) [e.g., Walker, 2012;Assink et al, 2014b] as well as uncertainties in the wave parameter estimation [Szuberla and Olson, 2004]. During the onset of the SSW, we note an increased number of low-frequency signals (5-10 s period) from northeasterly direction.…”
Section: Ecmwf Model Validation Using Continuous Infrasound Recordingsmentioning
confidence: 94%
“…While a general agreement between the observed and predicted microbarom azimuths is found, similar to earlier studies by Walker [2012] and Assink et al [2014b], differences up to~20°are often observed. These differences could be associated with approximations in long-range propagation modeling (azimuth uncorrected for transversal wind effects and range-independent atmospheric profiles) [e.g., Walker, 2012;Assink et al, 2014b] as well as uncertainties in the wave parameter estimation [Szuberla and Olson, 2004]. During the onset of the SSW, we note an increased number of low-frequency signals (5-10 s period) from northeasterly direction.…”
Section: Ecmwf Model Validation Using Continuous Infrasound Recordingsmentioning
confidence: 94%
“…Considering the uncertainties associated with the estimation of infrasound parameters, we have estimated the 95% confidence intervals for the estimated slowness values, using the method described by Szuberla and Olson [2004]. We have found that these uncertainties fall within the range of typical IMS infrasound arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the spread in the observed waveform parameters is not fully explained by these simulations. This could be explained by full-wave effects (for example, associated with small-scale fluctuations [Kulichkov, 2010]) or by uncertainties associated with the parameter estimation [Szuberla and Olson, 2004].…”
Section: Predictions and Observationsmentioning
confidence: 99%
“…7 This single-sensor failure mode has virtually no effect on srcLoc. Under srcLoc, there is no requirement for small clusters of sensors; with sufficient digitizers, sensors can be randomly scattered throughout the area of interest.…”
Section: Discussionmentioning
confidence: 99%